2021
DOI: 10.3389/fnhum.2021.677578
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Visual Feedback Using Immersive VR Affects Decision Making Regarding Hand Use With a Simulated Impaired Limb

Abstract: The long-term effects of impairment have a negative impact on the quality of life of stroke patients in terms of not using the affected limb even after some recovery (i.e., learned non-use). Immersive virtual reality (IVR) has been introduced as a new approach for the treatment of stroke rehabilitation. We propose an IVR-based therapeutic approach to incorporate positive reinforcement components in motor coordination as opposed to constraint-induced movement therapy (CIMT). This study aimed to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…It also showed that the use of virtual reality was more markedly used in rehabilitation and other digital healthcare. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…It also showed that the use of virtual reality was more markedly used in rehabilitation and other digital healthcare. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…The provision of optimal feedback, personalization, and incentivization of progress with a reward during VR-based training not only establishes a greater commitment to the therapeutic protocol but also facilitates a greater sense of agency to accelerate actual movement performance [48]. Incorporation of such reward-based movement training has been found to expedite protocol adaptation, skill-learning, and activity-dependent plasticity [48,49] (Figure 1).…”
Section: Mechanisms Of Vr Trainingmentioning
confidence: 99%
“…Recent studies on UL rehabilitation for stroke survivors found that the use of VR-based rehabilitation is more efficacious than dose-matched conventional therapy for regaining UL function [5,49]. However, the majority of studies available on VR-based UE rehabilitation focus on the proximal UE, with limited data on distal UE.…”
Section: Vr-based Rehabilitation For Distal Upper Extremitymentioning
confidence: 99%
“…2(b), the visual amplification in this research is done by displaying the virtual hand at α times linearly apart, that is, the virtual hand's position vector was increased α times in respect to the actual hand position vector, starting at a home position. It was found that the visual amplification affects the usage of the hand [9].…”
Section: Related Workmentioning
confidence: 99%
“…2. (a) and (b)Shows a participant wearing a HMD with a leap motion attached in front, the wrist weight is to simulate the affected arm of stroke patients[9]…”
mentioning
confidence: 99%